2015
DOI: 10.5114/wo.2014.47128
|View full text |Cite
|
Sign up to set email alerts
|

Review Biology of renal tumour cancer stem cells applied in medicine

Abstract: The present article highlights the diverse role of stem cells in normal kidney and renal cancer, with special emphasis on surface markers. Proteins such as CD105 and CD133 have been reported as being significant in clear cell renal cell carcinoma (ccRCC) cancer stem cells. The role of normal kidney progenitor cells and their surface markers is compared with the role of those surface markers in ccRCC. Subsequently, we state the current hypothesis about origin of tumour-initiating cells along with their clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…Many of these diseases have a high risk of relapsing within 5 years of surgical resection and this contributes heavily to disease mortality [54]. The cellular source of cancer relapse is currently unknown, although there is strong evidence to suggest that cancer stem cells may be responsible for this relapse in ccRCC and other cancers [55]. Recent work has shown that the production of H 2 S plays a key role in maintaining the stem-like phenotype of cancer cells through induction of stem cell factors OCT4 and NANOG, and through regulation of cellular energy production and oxidative stress [32].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these diseases have a high risk of relapsing within 5 years of surgical resection and this contributes heavily to disease mortality [54]. The cellular source of cancer relapse is currently unknown, although there is strong evidence to suggest that cancer stem cells may be responsible for this relapse in ccRCC and other cancers [55]. Recent work has shown that the production of H 2 S plays a key role in maintaining the stem-like phenotype of cancer cells through induction of stem cell factors OCT4 and NANOG, and through regulation of cellular energy production and oxidative stress [32].…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular markers have been used to identify CSCs and constitute valuable tools for tumor detection and diagnostic, prognostic, and predictive values, as well as determination of therapeutic targets [ 24 ]. Of note, no marker has been found so far that would be expressed only in CSCs [ 25 ].…”
Section: Cancer Stem Cells In Renal Cell Carcinomamentioning
confidence: 99%
“…A group of targeted agents selective against RCC has been developed and introduced in the clinic over the last decade (4,5). More recently, cancer stem cells (CSCs) or tumor-initiating cells have come into focus as potential treatment targets in solid tumors (6,7) and RCCs (8,9). Sunitinib (SU11248) is a multi-targeted kinase inhibitor of VEGFR-1, -2 and -3, PDGFR-β, mast/stem cell growth factor receptors (SCFR, c-Kit) and FMS-like tyrosine kinase 3 (FLT3) (10).…”
Section: Introductionmentioning
confidence: 99%